Peningkatkan Kemampuan Mengenal Bentuk Melalui Media Pasir Kinetic Pada Anak Kelompok B Di Raudhatul Athfal Samara Plus Kampar - Silvani, Lara; Guswanti, Nelia; Handayani, Fitri; Supri, Supri (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2023)
The research was classroom action research according to Kurt Lewin, Kemmis & Mc Taggart cycle model. The research was carried out in two cycles and each cycle was carried out in two meetings. In order to ensure the research, run well the researcher conducted on the stages that were passed in CAR such as; 1) planning/preparation, 2) implementation, 3) observation/observation, and 4) Reflection. The subjects in this study were teachers and 16 students of group B at RA (Islamic Kindergarten) Samara Plus in 2022/2023. While the object of this research was the ability to recognize shapes through Kinetic Sand media at group B of RA (Islamic Kindergarten) Samara Plus. The data collection instrument was the form of observation and student learning activities observation. After the data was collected through observation, the data was processed by using score and rating scales in the form of “stars” and checklists. Based on the results of this study, it proved that there is an improvement of the early childhood students in learning activities after the Cycle I and Cycle II through Kinetic Sand media at RA Samara Plus. Cycle I was the highest early childhood students’ ability to recognize shapes was still developed or two stars. In cycle II showed that the ability to recognize shapes had reached Expected developed. From 16 early childhood students, 14 early childhood students were at Expected developed and 2 of them at developed